Status-Role Relation of Communicants in Situations of Persuasion - E. N. Aznacheyeva; Y. V. Mamonova (Научный диалог)
The speech genre (SG) “persuasion” is investigated on the material of literary-fictitious dialogues in Russian literature. The relevance of the study is determined by the presence of many unresolved issues in the field of the theory of SG, the existence of transitional and hybrid forms of SG, the need to analyze socio-cultural factors of achieving communicative agreement. The novelty of the study is seen in the fact that there is a difference between SG “persuasion” in the narrow sense of the word (as one of the components in the communicative whole of a higher level) and in the broad sense - as a complex dialogical speech macrogenre of everyday communication, including, along with the actual persuasion, imperative statement, primary refusal (one or more) in the response, and the final statement with the final meaning of refusal or consent. Persuasion modelling depends on the initial mandatory subgenre, explicitness / implicitness of optional elements, repeatable structural components, achieving / not achieving illocutionary aims. Special attention is paid to the analysis of sociocultural factors of success / failure of speech actions: status-role relations of communicants, explicit and / or hidden illocutionary goal, the use of emotional and logical verbal means, the inclusion of elements of the related genre of coercion, a set of communicative strategies and tactics.